Interaction Of Grade And Metallurgy Simulations In Assessing Uncertainty For Ore Routing Determinations In The Gold Quarry Deposit - M. Baumann (Society for Mining, Metallurgy & Exploration, 2007)
Introduction Gold Quarry is one of the largest gold deposits in Nevada, located along the Carlin Trend, approximately seven miles north of Carlin, NV. Owned and operated by Newmont Mining Corporation, as of December 31, 2005, Gold Quarry had produced over 13 million ounces of gold. Multiple simulations were constructed for gold and metallurgical variables using the Stepwise Conditional Transformation method. Analyses of these simulations have been used for a variety of purposes, including an assessment of uncertainty with various ore types. This assessment provides insight for improved modeling and reconciliation. Geological Framework Gold Quarry is a large, low-grade disseminated gold deposit hosted in Silurian-Devonian aged sediments at the Chukar/Alunite-Good Hope fault intersection. Gold bearing hydrothermal fluids appear to have migrated upwards along the Chukar/Alunite and Deep Sulfide Feeder faults and then moved outward along favorable stratigraphic horizons and structural intersections.